What Ever Happened to the Kuznets Curve? Is it Really Upside Down? - Glomm, Gerhard (Journal of Income Distribution®, 1998)
Kuznets (1955) embarked on a research program whose goal was to find the determinants of the long run levels and trends in income inequality and the relationship between income inequality and economic growth. Recently a small body of theoretical work has developed which tries to obtain the inverted U hypothesis as an equilibrium outcome in dynamic general equilibrium model. One of the types of general equilibrium models which can deliver a Kuznets curve is a model which allows for persistent migration out of one sector, e.g. agriculture, into another – e.g. manufacturing. Most industrialized countries have not only experienced shifts from agriculture to manufacturing, but also into services, especially associated with information technologies. This is responsible for the rise in inequality. If such a model of the arrival of new opportunities is correct, we would not expect to find a Kuznets curve, right side up or up-side down. Here we review the empirical evidence regarding the Kuznets curve.